2017
DOI: 10.2337/db16-1281
|View full text |Cite
|
Sign up to set email alerts
|

RAGE-Aptamer Blocks the Development and Progression of Experimental Diabetic Nephropathy

Abstract: The interaction of advanced glycation end products (AGEs) and their receptor (RAGE) plays a central role in diabetic nephropathy. We screened DNA aptamers directed against RAGE (RAGE-aptamers) in vitro and examined the effects on the development and progression of diabetic nephropathy in streptozotocin-induced diabetic rats. RAGE-aptamer bound to RAGE with a of 5.68 nmol/L and resultantly blocked the binding of AGEs to RAGE. When diabetic rats received continuous intraperitoneal injection of RAGE-aptamer from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 51 publications
4
89
1
1
Order By: Relevance
“…Recently, we reported that a DNA aptamer, a short and single-stranded DNA, directed against RAGE (RAGE aptamer) inhibited the binding of AGE to RAGE and attenuated the development and progression of streptozotocin-induced diabetic nephropathy in rats and deoxycorticosterone acetate/salt-induced renal injury in mice [17, 18]. We examined the inhibitory effects of the RAGE aptamer on PDGF-induced proliferation of PASMCs.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported that a DNA aptamer, a short and single-stranded DNA, directed against RAGE (RAGE aptamer) inhibited the binding of AGE to RAGE and attenuated the development and progression of streptozotocin-induced diabetic nephropathy in rats and deoxycorticosterone acetate/salt-induced renal injury in mice [17, 18]. We examined the inhibitory effects of the RAGE aptamer on PDGF-induced proliferation of PASMCs.…”
Section: Resultsmentioning
confidence: 99%
“…104-107 Furthermore, RAGE-aptamers promoted regression of experimental diabetic nephropathy in type 1 diabetic animals, attenuated melanoma growth and metastasis in nude mice, and ameliorated renal injury in hypertensive mice. [108][109][110] These findings suggest that blockade of the AGE-RAGE axis by AGE-or RAGE-aptamers may be a therapeutic target for CVD.…”
Section: Circulating Levels Of Ages and Cvdmentioning
confidence: 90%
“…Moreover, these phenotypes were prevented by the administration of an AGE inhibitor, indicating that the AGE-RAGE signal is an effective target for overcoming DKD. Other studies have evaluated the effects of the specific inhibition of RAGE with DNA aptamer and demonstrated that RAGE-aptamer attenuates the development of experimental DKD by inhibiting oxidative stress [33,34].…”
Section: The Age-rage Pathwaymentioning
confidence: 99%